Social Capital Theory, Social Exchange Theory, Social Cognitive Theory, Financial Literacy, and the Role of Knowledge Sharing as a Moderator in Enhancing Financial Well-Being: From Bibliometric Analysis to a Conceptual Framework Model - Thomas, Asha; Gupta, Vikas (Frontiers in Psychology, 2021)
A person’s financial well-being (FWB) is the complete contentment gained from one’s present financial condition. This has a powerful impact on the entire achievement of an employee’s “well-being.” Researchers, financial analysts, financial planners, educationists, and economists have explored the “enablers” to improve employees’ living standards by investigating the possible “FWB” resources for decades. There is no literature available to show the connection between social capital theory, social exchange theory (SET), social cognitive theory (SCT), financial literacy and FWB, and employees’ financial knowledge sharing a moderator to expand the complete FWB.